If y=x+tanx then prove that cos^2x(y2)-2y+2x=0 where y2 is the second derivative...plz help me out.

2 answers

y=x+tan(x)
y'=1+sec(x)^2
y"=0+2sec(x)*(-1/cos²(x))(-sin(x))
=sec²(x)tan(x)

=>
cos²(x)y"-2y+2x
=2cos²(x)sec²(x)tan(x)-2(x+tan(x)+2x
=2tan(x)-2x-2tan(x)+2x
=0
Should read:

y"=0+2sec(x)*(-1/cos²(x))(-sin(x))
=2sec²(x)tan(x)
Similar Questions
  1. Derivative of y=sec(tanx)?I don't get how it is secxsecx*secxtanx*tanxtanx. Where does an extra tanx come from? Derivative of
    1. answers icon 1 answer
  2. Evaluate the indefinite integral.∫ sec^3x tanx dx I let u=tanx took derivative.. du=sec^2x dx ..now what??
    1. answers icon 1 answer
  3. Prove cotx-1/cotx+1 = sec2x - tan2xI prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx
    1. answers icon 1 answer
    1. answers icon 5 answers
more similar questions